Single cell dissection reveals SFRP2+ fibroblasts amplifying inflammatory responses in oral lichen planus - Cheng, Juehua; Liu, Jia; Zhu, Yuchi; Yang, Jingjing; Geng, Yanlin; Fan, Yuan (Frontiers in Immunology, 2025)
ObjectivesOral lichen planus (OLP) is a chronic inflammatory mucosal disease with an incompletely understood pathogenesis. This study aimed to investigate the role of disease-specific fibroblasts in OLP.MethodsWe performed single-cell RNA sequencing on buccal mucosa of 4 OLP patients and one healthy control. Additionally, mRNA expression and immunofluorescence staining were analyzed in primary fibroblasts from 51 OLP patients and 24 healthy individuals. The spatial cellular interactions were assessed using multiplex immunofluorescences in OLP tissues.ResultsUsing single-cell RNA sequencing, we identified SFRP2+ fibroblasts as the origin of inflammatory fibroblasts in OLP. A subset of SFRP2+ fibroblasts specifically expressed Wnt5a and was implicated in antigen processing and presentation pathway in OLP. Furthermore, SFRP2+Wnt5a+ fibroblasts amplified and maintained the local immune inflammation by interacting with CD8+ T cells and epithelial cells. Compared to the healthy control group, upregulated expressions of pro-inflammatory molecules (CXCL12, CXCL14) and antigen presenting associated molecules (HLA-A, HLA-B, HLA-C and ERAP2) were displayed in OLP group at mRNA level. Colocalization of SFRP2 and Wnt5a was displayed in the primary cultured fibroblasts of OLP in vitro. Besides, SFRP2+ Wnt5a+ fibroblasts were located around CD8+ T cells in the superficial layer of the lymphocyte infiltration zone.ConclusionsOur findings reveal the heterogeneity and pathogenic mechanisms of fibroblasts in OLP, providing new insights into the cellular drivers of chronic inflammation in OLP.